Biological aspects and daily rhythm of activities of Porasilus barbiellinii predator of the froghopper - Bueno, Vanda Helena Paes (Pesquisa Agropecuaria Brasileira, 2014)
This work studied the biological aspects and daily rhythm of the activities (mating, oviposition, searching and predation) of Porasilus barbiellinii Curran, 1934 (Diptera, Asilidae) predator of the froghopper Deois flavopicta (Stal, 1854) (Homoptera, Cercopidae). The field study was carried out in a pasture of Brachiaria decumbens Stapf located in the municipality of Três Corações, State of Minas Gerais, Brazil, in three five-day periods, for nine hours a day. The laboratory observations were conducted in the Entomology Laboratory of Crop Protection Department of ESAL, Lavras, MG (temperature 25 ± 1°C; relative humidity 70 ± 10% and photophase fourteen hours). The egg period was an average seven days and the larvae took, on average two minutes to free themselves from the corium. A peak of activity of mating occurred from eight nine a.m. and other from four - five pm. High temperature favored oviposition which took place most frequently between eleven a.m. and two p.m. The asilid flies exercised its searching activity from eight a.m. - five p.m. The most significant time for predation by both males and females was from two - three p.m.